Co-creation and brand happiness: insights from a Korean perspective - Nobi, Benjamin (The Journal of consumer marketing, 2024)
Purpose Extant literature has extensively explored the factors driving consumer emotions. This study aims to contribute to the ongoing discourse by elucidating the influence of co-creation on consumer emotions. Specifically, this investigation seeks to probe how co-creation activities, orchestrated by firms, impact consumers' emotional experiences, with a particular emphasis on brand happiness. By addressing this research gap, the author aims to shed light on the understudied domain of co-creation's effects on consumer emotions, notably brand happiness, a subject that warrants further investigation in prior scholarly works. Design/methodology/approach Using surveys as the primary data collection method, the author assesses consumer perceptions, emotions and brand social responsibility. The initial study aims to discern the mediating role of brand social responsibility in the link between co-creation and brand happiness. Subsequently, the second study evaluates the moderating effect of brand social responsibility in the relationship between co-creation and brand happiness. These systematic investigations enable us to uncover the intricate dynamics between co-creation, brand social responsibility and consumers' emotional experiences, culminating in a deeper understanding of the phenomena at play. Findings The empirical findings of this study unveil the substantial impact of co-creation on consumers' brand happiness. Engaging in co-creation with a brand leads to a notable elevation in consumers' perceptions of the brand's social responsibility. Importantly, this heightened perception of brand social responsibility positively influences their emotional affinity toward the brand, resulting in increased happiness. Furthermore, this investigation sheds light on an intriguing aspect – the role of an individual's personal expressiveness. It accentuates how personal expressiveness acts as an augmenting factor, strengthening the effect of co-creation on brand happiness. Originality/value This research addresses the relatively underexplored topic of brand happiness, which constitutes a fundamental aspect of consumers' experiences. By shedding light on the intricate interplay between co-creation, consumer emotions and happiness, this research introduces an essential theoretical framework that emphasizes the pivotal role of co-creation in driving consumer emotional experiences and overall happiness. As such, this study presents a comprehensive and valuable contribution to the growing body of knowledge in consumer behavior and marketing.